Pentingnya Kecerdasan Emosional Pendidik Dalam Meningkatkan Pendidikan Karakter - Anggi Rivana (Jurnal Asy-Syukriyyah, 2019)
Emotional intelligence is a skill on how to manage emotions to be better for themselves and others, emotional intelligence is divided into two namely intrapersonal intelligence (ability to understand intentions, motivations, moods, temperament and desires of others) and interpersonal (ability to form a a careful and self-referring model of oneself and the ability to use capital as a tool to lead an effective life)